Stomach content analysis of mesopelagic fish from the southern Kerguelen Axis. (April 2020) - Riaz, Javed; Walters, Andrea; Trebilco, Rowan; Bestley, Sophie; Lea, Mary-Anne
Abstract: Mesopelagic fish represent an important trophic link between zooplankton and higher order predators in Southern Ocean food webs. Information on their feeding habits is still sparse, representing a key area of uncertainty in efforts to understand and model Southern Ocean food web dynamics. We used visual assessment of stomach contents to characterise the diets of three myctophids ( Electrona antarctica, Gymnoscopelus braueri, Krefftichthys anderssoni ) and one bathylagid ( Bathylagus antarcticus ) over the southern extension of the Kerguelen Plateau ('southern Kerguelen Axis'), a highly productive area of both biological and economic importance in the Indian sector of the Southern Ocean. Diets of all four species were dominated by euphausiids, amphipods, copepods and fish. Bathylagus antarcticus also preyed upon a high proportion of soft-bodied organisms. There was strong evidence for dietary variability both within and between species, and this variability was driven by latitudinal variation in zooplankton assemblages. Size-based shifts in diet were apparent, with larger individuals of myctophid and bathylagid species consuming larger prey. Linear mixed effects models also demonstrated that the weight of prey consumed increased in relation to predator weight. Dietary information presented here advances our understanding of the mesopelagic components of Southern Ocean food webs, which will improve the development of food web models for the region.